THE IMPACT OF TECHNIQUES AND TRANSLATION IDEOLOGY ON THE CLARITY OF PRAGMATIC MEANINGS TRANSLATION OF THE QUR’ANIC IMPERATIVE VERSES - Al Farisi, Mohamad Zaka (Indonesian Journal of Applied Linguistics, 2018)
One of the stylistic features of the Qur?an is the existence of imperative verses that have certain pragmatic meanings. The feature often makes the Indonesian translation of these verses complex. This is mainly related to the fulfillment of the aspect of clarity in translation. This study aims to reveal the subtle translation of imperative verses of the Qur?an with certain pragmatic meanings. This descriptive-evaluative study used the design of embedded case study because the findings apply only to the imperative verses that serve as the research sample. The sample of the study was chosen purposively from the Qur?anic verses that contain imperative speech. They are imperative verses that have certain pragmatic meanings, such as al-tahdid (threatening), al-ihanah (humiliating), and so forth. The focus of the study is on the subtle translation of imperative verses contained in the translation version by UMT. In general, based on the responses of respondents and the test results, the translations of imperative verses by UMT produce acceptable clarity.